Genetic glucocorticoid receptor variants differ between ethnic groups but do not explain variation in age of diabetes onset, metabolic and inflammation parameters in patients with type 2 diabetes - Ahdi, Mohamed; Gerards, Maaike C.; Smits, Paul H.M.; Meesters, Eelco W.; Brandjes, Dees P. M.; Nieuwdorp, Max; Gerdes, Victor E. A. (Frontiers in Endocrinology, 2023)
Aims: The effect of excess glucocorticoid receptor (GR) stimulation through glucocorticoid medication or cortisol on glucose metabolism is well established. There are genetic GR variants that result in increased or decreased GR stimulation. We aimed to determine the prevalence of genetic GR variants in different ethnic groups in a cohort of patients with type 2 diabetes, and we aimed to determine their association with age of diabetes onset and metabolic and inflammation parameters.Methods: A cross-sectional analysis was performed in a multiethnic cohort (n = 602) of patients with established type 2 diabetes. Polymorphisms in the GR gene that have previously been associated with altered glucocorticoid sensitivity (TthIIII, ER22/23EK N363S, BclI and 9β) were determined and combined into 6 haplotypes. Associations with age of diabetes onset, HbA1c, hs-CRP and lipid values were evaluated in multivariate regression models.Results: The prevalence of the SNPs of N363S and BclI was higher in Dutch than in non-Dutch patients. We observed a lower prevalence of the SNP 9β in Dutch, South(East) Asian and Black African patients versus Turkish and Moroccan patients. We did not detect an association between SNPs and diabetes age of onset or metabolic parameters. We only found a trend for lower age of onset and higher HbA1c in patients with 1 or 2 copies of haplotype 3 (TthIIII + 9β).Conclusions: The prevalence of genetic GR variants differs between patients of different ethnic origins. We did not find a clear association between genetic GR variants and age of diabetes onset or metabolic and inflammation parameters. This indicates that the clinical relevance of GR variants in patients with established type 2 diabetes is limited.